Special Relativity - E. Schroder Ulrich (World Scientific, 1990)
This book provides a thorough discussion of the concepts and main consequences of special relativity. Treated in detail are the Lorentz transformations, their kinematical consequences (the so-called paradoxes), relativistic mechanics, electrodynamics as an example of a relativistic field theory, and the principal features of relativistic hydrodynamics. The book offers a logical development of special relativity from Einstein's principle of relativity alone; arrives at the essential statements of the theory by a direct approach — this emphasis is different from that of most books; and offers a concise introduction to tensor calculus as needed in special relativity. A selection of problems and documentation of the experimental tests of special relativity are given.